ANALYSIS OF INDONESIA ECONOMIC GROWTH BASED ON INVESTMENT VALUE AND HUMAN DEVELOPMENT INDEX USING AN ECONOMETRIC APPROACH - Endah Setyowati (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2022)
The study aims to determine the effect of the Human Development Index (HDI) variable and investment variables which include Domestic Investment and Foreign Investment on the Gross Regional Domestic Product (GRDP) of 34 provinces in Indonesia in 2015-2019. The method used in this research is panel regression analysis. The results of the study indicate that the best panel data regression model for modeling GRDP is the Random Effect Model (REM). Based on the model formed, it is known that the variables HDI, Domestic Investment, and Foreign Investment have a significant positive effect on GRDP. These results are consistent with the theory and hypothesis that the higher the value of the HDI, Domestic Investment, and Foreign Investment, the higher the value of the GRDP variable. The coefficient of determination shows a moderate value of 58.9%, so it is suspected that there are other variables that can affect GRDP. Based on the regression model formed, if all independent variables have the same value for all provinces, then the province with the highest GRDP value is Jakarta.